Fatigue crack nucleation and small crack growth in an extruded 6061 aluminum alloy. (February 2019) - McCullough, R.R.; Jordon, J.B.; Allison, P.G.; Rushing, T.; Garcia, L.
Highlights: Strain-life experiments were conducted for AA6061 in two heat treatments. Striation spacing was measured up to the point of cracked intermetallic particles. Micromechanical simulations estimated strain fields at intermetallic particles. A multi-stage fatigue model captured the fatigue nucleation and small crack growth. Abstract: A combined synergistic experimental and computational approach has been employed to elucidate the underlying mechanisms for fatigue crack nucleation and microstructurally small crack growth in a 6061 aluminum alloy as a function of two heat treatments: a T6 treatment in its as-received state and a custom annealing condition. In this study, fully-reversed fatigue experiments of the 6061 aluminum alloy in two heat treatment conditions were performed in strain-control. Post-mortem analyses of the fracture surfaces were conducted to quantify sources of crack nucleation and microstructurally small crack growth. In particular, striation spacing in the small crack stage was measured up to the point of nucleation at cracked intermetallic particles and/or clusters of cracked particles. To capture the mechanics of fatigue crack nucleation, the local strain field at cracked intermetallic particles were estimated using micromechanics finite element simulations. Both the finite element approach and the experimental results were used in the implementation of a multi-stage fatigue model in order to correlate the microstructure-influenced mechanical response, including fatigue crack nucleation and small crack propagation contributions on fatigue behavior in 6061 aluminum alloy under two heat treatments.